Istirâtijiyah Ta’lîm al-Lughah al-Arabiyyah li Tarqiyyah al-Kafâ’ah al-Ittiṣâliyah lada Ṭulâb - Rani Ismil Hakim; Syaipuddin Ritonga; Bambang Bambang (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Objective- Reveal the strategies teachers use in improving Arabic communication skills among learners. This is important to do considering that the ability of students in Islamic boarding schools in Arabic is often not found a balance between ability in grammatical aspects and communication skills. Design / Methodology / Qualitative- Approach is used as a research method, this is because data and typical do not require statistical analysis. The research was carried out at the Daruttawhid Jambur Mandailing Natal Islamic Boarding School. The research informants were Arabic teachers and purposively selected learners. Data are collected by observation techniques, interviews and documentation studies, the data that has been collected are analyzed interactively.  Findings- The results of the study found that to improve the communication skills of Arabic students at Daruttawhid Jambur Islamic boarding school, the use of Arabic does not only take place in the classroom, but the teacher also guides and directs students to make Arabic a communication tool in life in the Islamic boarding school environment. Keywords: Communication Skills, learning strategies, language activities. Teachers use communicative strategies in improving Arabic communication skills, namely making Arabic a communication tool in formal learning and daily life.  Research Limitations/Implications- Researchers have not conducted trials of the strategies used by Arabic teachers. Therefore, the next research or subsequent researchers can conduct studies on these aspects. The implication of the findings of this study is that the combination of grammatical knowledge that is the strength of pesantren can be balanced with the use of daily Arabic, so that students have communication skills.